Effects of Using 5e Learning Cycle Cooperate with Songs on Science Learning Achievement and Positive Learning Atmosphere of Lower Secondary School Students, Bangkok Metropolitan - Khauanpuck, Amphon; Kaewdee, Sakolrat (Scholar: Human Sciences, 2017)
This study was a quasi-experimental research. The aims of this study were to evaluate the science learning achievement and positive learning atmosphere of a group of students that studied with a 5E learning cycle cooperate with songs; in comparison with the control group that learned from a traditional lecture method. The student groups were two classes of MathayomSuksa 1 (grade-7) students of Debsirin School, Bangkok, in the academic year 2015. The students taught with a 5E learning cycle cooperate with songs had a mean science learning achievement score that was significantly higher than the control group taught by the traditional lecture method and above the criterion score (70%). In addition, the positive learning atmosphere of the classroom that was taught by the 5E learning cycle cooperate with songs was rated “good”, as opposed to the rating of the classroom that learned through the traditional lecture method.